TINDAK TUTUR DIREKTIF PADA UPACARA LAMARAN MASYARAKAT LAMPUNG KOMERING - Nurhasanah, Nurhasanah (JURNAL PESONA, 2017)
This research is study of speech act  in conversation of event wedding proposal of Komering, Lampung society. This study focused on directive Speech Act. The primery data was video of wedding proposal  of Komering, Lampung society. Then the secondary data was archieves book wedding proposal  of Komering, Lampung society.  This study described directive speech act which used by the speaker. The result obtains four directive speech act which were expressed in wedding proposal ceremony in Komering, Lampung society. Those are directive speech act of demands, expectations, advice, and orders.